2022
DOI: 10.1037/cdp0000538
|View full text |Cite
|
Sign up to set email alerts
|

Racial and gender discrimination by teachers: Risks for Black girls’ depressive symptomatology and suicidal ideation.

Abstract: Objectives: The present study examines how race and gender-specific factors (i.e., racial centrality and gender role beliefs) serve as protective assets against the harmful impact of racial and gender discrimination on depressive symptomatology and suicidal ideation for Black girls. Method: Our sample included 232 Black girls ages 15–17 years old (Mage = 16.85) from a socioeconomically diverse community context. Results: Our findings revealed that racial and gender discrimination from teachers was associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 101 publications
0
8
0
1
Order By: Relevance
“…There was an increase in depressive symptoms on the day following instances of racial discrimination for youth that experienced levels of low public regard as compared to participants' average level of public regard (Seaton & Iida, 2019). Butler-Barnes et al (2022) found that lower levels of racial centrality and higher levels of perceived teacher racial discrimination were associated with higher levels of depressive symptoms among Black girls. Further, supporting nontraditional gender role beliefs with higher levels of perceived teacher racial discrimination was associated with lower levels of suicidal ideations (Butler-Barnes et al, 2022).…”
Section: Intrapersonal Factorsmentioning
confidence: 80%
“…There was an increase in depressive symptoms on the day following instances of racial discrimination for youth that experienced levels of low public regard as compared to participants' average level of public regard (Seaton & Iida, 2019). Butler-Barnes et al (2022) found that lower levels of racial centrality and higher levels of perceived teacher racial discrimination were associated with higher levels of depressive symptoms among Black girls. Further, supporting nontraditional gender role beliefs with higher levels of perceived teacher racial discrimination was associated with lower levels of suicidal ideations (Butler-Barnes et al, 2022).…”
Section: Intrapersonal Factorsmentioning
confidence: 80%
“…However, this may be partially due to the fewer cases of discrimination from teachers. Prior studies have found that teachers play a critical role in adolescent development and mental health [ 53 , 54 ]. Further studies should continue to investigate the relationships between ethnic discrimination perpetuated by teachers and adults outside school and binge eating.…”
Section: Discussionmentioning
confidence: 99%
“…Research consistently documents associations between internalized and interpersonal forms of stigma and mental health problems in multiple groups of stigmatized youth (e.g., youth of Color, girls, sexual minority youth; Bailey et al, 2021;Butler-Barnes et al, 2022;Chodzen et FUTURE DIRECTIONS IN STIGMA AND YOUTH MENTAL HEALTH TREATMENT 5 al., 2019;Price-Feeney et al, 2021;Reed et al, 2019;Rogers et al, 2022;Watson et al, 2019;Weeks & Sullivan, 2019). Relatively fewer studies have examined structural stigma in youth, but scholars have found associations between structural stigma and youth mental (e.g., anxiety, depression, suicidality; Beccia et al, 2022;Duncan & Hatzenbuehler, 2014;Hatzenbuehler, 2011;Hatzenbuehler & Keyes, 2013;Saewyc et al, 2020;Torres et al, 2018) and behavioral (e.g., smoking, alcohol/substance use; Eisenberg et al, 2020;Hatzenbuehler et al, , 2015Watson et al, 2020Watson et al, , 2021 health concerns.…”
Section: Future Directions In Mental Health Treatment With Stigmatize...mentioning
confidence: 99%